ESTUDIO DE FACTIBILIDAD DE UNA APLICACIÓN MÓVIL PARA LA CONSULTA DE LIBROS EN LA BIBLIOTECA DE LA F.A.F.I - ALARCÓN CEDEÑO, CLARA INES (2018)
Currently, mobile technologies are at their peak of expansion. These new mobile devices provide new forms of communication and interaction between users and the machine, thanks to the evolution they have had both in the hardware and software of these mobile devices, its use is very broad in several fields, such as multimedia , the use of sensors, the consumption of web services and internet browsing. The Faculty of Administration, Finance and Information Technology makes use of different means of communication and information such as Moodle, SAI, Institutional Mail, Website among others, which at present have been able to satisfy the academic needs of the students, the changes that generate with the new information technology (ICTs) are present in all areas of our lives as learning tools, therefore the School of Finance and Information Management due to the educational context consider updating their academic tools to be able to Improve this way the activities in the Library of the FAFI, through a mobile application which students can consult the books through their mobile device. The objective of this case study is to determine the feasibility of a mobile application for the book consultation in the F.A.F.I Library, which will allow students as teachers to keep informed of Library activities.